Simply keto - Ryan, Suzanne (Blogger) (Victory Belt Publishing Inc., 2017)
Simply Keto is a practical and easy-to-understand guide to the ketogenic diet with more than 100 low-carb, high fat recipes and advice from popular blogger Suzanne Ryan.